Justification of Averaging Method for Multifrequency Impulsive Systems - Petryshyn, R. I.; Sopronyuk, Т. M. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We prove new theorems on the justification of the averaging method for multifrequency oscillation systems with pulse influence at fixed times.